Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3389/fpls.2017.01142
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms behind the Physiological Resistance to Intense Transient Warming in an Iconic Marine Plant

Abstract: The endemic Mediterranean seagrass Posidonia oceanica is highly threatened by the increased frequency and intensity of heatwaves. Meadows of the species offer a unique opportunity to unravel mechanisms marine plants activate to cope transient warming, since their wide depth distribution impose divergent heat-tolerance. Understanding these mechanisms is imperative for their conservation. Shallow and deep genotypes within the same population were exposed to a simulated heatwave in mesocosms, to analyze their tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 91 publications
3
57
0
Order By: Relevance
“…Functional enrichment analysis showed that the early (T1) response of C‐plants to temperature increase included the activation of biological processes previously reported in the short‐term heat response of P. oceanica (Marín‐Guirao et al, ), and encompassed the modification of primary and secondary metabolism, protein folding and cell wall reorganization (Figure , Table a). The response was more intense after 6 weeks of heat exposure (T2) as reflected by the number of DEGs.…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…Functional enrichment analysis showed that the early (T1) response of C‐plants to temperature increase included the activation of biological processes previously reported in the short‐term heat response of P. oceanica (Marín‐Guirao et al, ), and encompassed the modification of primary and secondary metabolism, protein folding and cell wall reorganization (Figure , Table a). The response was more intense after 6 weeks of heat exposure (T2) as reflected by the number of DEGs.…”
Section: Resultsmentioning
confidence: 84%
“…The newly assembled transcriptome was combined with three previously published P. oceanica transcriptomes using Trinity to generate a comprehensive and representative transcriptome of the species. A whole description of methods and bioinformatic analysis of these three de novo assemblies can be found elsewhere (D'Esposito et al, ; Entrambasaguas et al, ; Marín‐Guirao et al, ). In order to remove intra‐assembly redundancy, each individual assembly was firstly processed by cd‐hit‐est v4.6.7 (Huang, Niu, Gao, Fu, & Li, ) with 100% identity to remove identical contigs with a word size of 10.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations